Pengembangan Modul Ekosistem Berbasis Paradigma Wahdatul Ulum untuk Siswa Kelas X MAS Al-Wasliyah Percut - Deni Veronika Sihombing; Kartika Manalu; Riris Nurkholidah Rambe (Mu'allim, 2023)
Making products in the form of learning modules is the development of the Wahdatul Ulum Paradigm-Based Ecosystem Module. The resulting modules are used as instructional content. This author developed a product in the form of a wahdatul ulum-based module which was carried out at the MAS Al-Wasliyah Percut school with ecosystem material for class X SMA/MA students because modules detailed with the wahdatul ulum paradigm concept are generally not available in biology textbooks. The layout plan contained in this module is expected to be able to encourage students, be cool and be interested in understanding the use of the module because it displays lots of interesting pictures. This increase in exploration takes advantage of the progress of Research and Development (Innovative Work) with the 4D plan which has four phases, namely Characterize, Plan, Advancement, and Spread. Based on the assessment results from experts and also students, it is known that the development of environmental modules is very possible to be used as teaching materials. Media experts scored 87.50 percent, material experts scored 92.30 percent, and religion experts scored 85.41 percent in their due diligence assessment. Ecosystem modules based on the wahdatul ulum paradigm for class X SMA/MA students deserve to be used as additional teaching materials for the learning process, according to the assessment results, namely 91.66% for Biology teachers and 90.88% for students.